2023
DOI: 10.1186/s12905-023-02367-3
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in healthcare-seeking behavior among women with pelvic organ prolapse: a systematic review and narrative synthesis

Abstract: Introduction Pelvic organ prolapse (POP) affects women’s quality of life in various aspects. However, evidence on the healthcare-seeking behavior of women with POP is limited. Therefore, this review aimed to identify and synthesize the existing evidence on the healthcare-seeking behavior among women with POP. Methods This systematic review and narrative synthesis of the literature on healthcare-seeking behavior among women with POP was conducted fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…It is noteworthy that even in highly developed countries, one-fourth of patients hide their ailments. This depends on the health awareness of patients and is lower in countries with a low degree of economic development [ 18 ]. This phenomenon may further perpetuate the feeling of abandonment and social exclusion and thus lead to mood disorders and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that even in highly developed countries, one-fourth of patients hide their ailments. This depends on the health awareness of patients and is lower in countries with a low degree of economic development [ 18 ]. This phenomenon may further perpetuate the feeling of abandonment and social exclusion and thus lead to mood disorders and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of the analysis in this study have confirmed the positions of literature on the influence of the socio-economic characteristics of health-seeking individuals on their health-seeking behaviours-particularly regarding their access to quality healthcare. The levels of enlightenment (formal education) and income are socio-economic factors determining people's choice of where to go for quality healthcare [91][92][93]. These factors determine health seekers' ability to secure health services in facilities they perceive to offer the best service.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer than 25% of males and females with sexual symptoms seek the help of a medical professional [ 14 ]. The level of help-seeking behaviour for POP ranges from 21.3% to 73.4%, with the lower levels in low-income countries [ 15 ].…”
Section: Introductionmentioning
confidence: 99%